Ranup Lampuan Dance and Islamic Education : Instilling Islami Character for Children at MIN 13 Nagan Raya - Sumarni; Khairuddin Hasan; Masni (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The research aims to describe the cultivation of Islamic character in learning local wisdom based on the Aceh Ranup Lampuan Traditional Dance at MIN 13 Nagan Raya. The research approach used is qualitative with a descriptive type, the research subjects are Religion Teachers, Arts Teachers and students participating in traditional dance activities in forming students' character. Test the credibility of the data using source triangulation, testing process, analysis and conclusions. Data analysis is carried out in a cyclical model starting from data collection, reducing, clarifying, concluding and interpreting all the information obtained selectively. The results of the research show that the application of Ranup Lampuan dance learning at Min 13 Nagan Raya is very helpful in the process of cultivating Islamic character for children, and can also show that dance activities are not only a means of preserving culture, but are also effective in shaping the character of students to have noble morals. so that it has an impact on the formation of students' character in the context of Islamic religious education.